Characterization of Vaginitis Among Women Complaining of Genital Tract Symptoms - Muheddin Kareem, Hemin; Saed Qadir, Muhammed; Bakr Karim, Safa; Jawhar Ali, Solaf (Kurdistan Journal of Applied Research, 2020)
Vaginitis is the inflammation of the vagina as a result of a change in the balance of normal flora affecting women of reproductive age. It is one of the most frequent reasons that women visit clinics. The objective of this study was to determine the importance of laboratory diagnosis methods in the treatment of the disease and to study the symptoms and risk factors associated with vaginitis among women with genital tract symptoms. Vaginal swabs were collected from 50 women attending Maternity hospital and Chwarchra dormitory camps in Sulaimani city. Samples were examined microbiologically and causative agents were isolated. All relevant clinical information such as patient demographic profiles, socioeconomic variables, risk factors and symptoms have been collected by questionnaire based study. Different species of microorganisms were isolated from vaginal samples including yeast and bacteria. Culture analysis and gram stain had shown that bacterial vaginosis was 22%, while the rate of yeast infection was 16%. The higher percentage was 62% for the normal flora (Lactobacillus). Microscopic examination of patient’s vaginal swabs revealed that 63.6% of infectious group had high level of epithelial cells (>10), while the most patients with non-infectious vaginitis had (10) or less epithelial cell in the microscopic field. The presence of epithelial cell was significantly associated with infectious vaginitis (p-value 0.04). Most patients were aged between 25-35 years. The result showed a significant association between infectious vaginosis with education level (p-value 0.02). The most common symptom present among patients with infectious vaginitis group was itching (38.5%) and smelly discharge (40%). The majority of women had history of previous infections in both infectious and non-infectious vaginitis groups. Furthermore, there was different types of vaginitis including infectious vaginitis (bacterial and yeast infection) and non-infectious vaginitis. Therefore, it is essential to perform laboratory examination for the patients to detect the causative agents of vaginitis, and ensure the most appropriate treatment can be administered. In addition, the treatment of vaginitis can be done by topical application of Lidocaine 5% ointment (as a local anesthetic) nightly for seven weeks has been shown to decrease the pain of vaginitis in women.